2020
DOI: 10.3390/nu12061779
|View full text |Cite
|
Sign up to set email alerts
|

Maternal Microbiota, Cortisol Concentration, and Post-Partum Weight Recovery Are Dependent on Mode of Delivery

Abstract: The importance of the maternal microbiota in terms of the initial bacterial seeding has previously been highlighted; however, little is currently known about the perinatal factors that could affect it. The aim of this study was to evaluate the effects of various delivery-related factors on the intestinal microbiome at delivery time and on post-partum weight retention. Data were collected from mothers (n = 167) during the first four months post-partum. A subset of 100 mothers were selected for the determination… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
5
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 91 publications
3
5
0
1
Order By: Relevance
“…Interestingly, the microbiome appeared to show signi cant discrepancies in the vaginal uid samples of pregnant women who were subjected to different labour modes. This conclusion was consistent with Marta Selma-Royo et al [21] and Romero R et al [22], which described the variations occurred during gestation, mainly in the intestinal and vaginal microbiomes. These studies also indicated that delivery mode signi cantly affected the maternal microbiota composition at delivery.…”
Section: Discussionsupporting
confidence: 91%
“…Interestingly, the microbiome appeared to show signi cant discrepancies in the vaginal uid samples of pregnant women who were subjected to different labour modes. This conclusion was consistent with Marta Selma-Royo et al [21] and Romero R et al [22], which described the variations occurred during gestation, mainly in the intestinal and vaginal microbiomes. These studies also indicated that delivery mode signi cantly affected the maternal microbiota composition at delivery.…”
Section: Discussionsupporting
confidence: 91%
“…Children microbiota clustering was generated at the genus level as described previously [ 19 ] using the phyloseq [ 20 ], cluster [ 21 ], MASS [ 22 ], clusterSim [ 23 ], and ade4 R packages [ 24 ]. Briefly, the Jensen–Shannon distance and partitioning around medoid (PAM) clustering were used.…”
Section: Methodsmentioning
confidence: 99%
“… Nunn et al (2021) considered that the decrease in relative abundance of Lactobacillus in postpartum women might be associated with the maternal estrogen levels falling precipitously after placenta removal. Selma-Royo et al (2020) found that the mode of delivery influenced vaginal microbiota composition manifesting the changes of relative abundance of various genera. Therefore, it is worthwhile further exploring factors contributing to the changes of vaginal microbiota, especially in postpartum women.…”
Section: Discussionmentioning
confidence: 99%